Uncovering microbial community assemblages associated with soil of the South-East Pahang Peat Swamp Forest - Muhammad Aidilfitri Mohamad Roslan (Kulliyyah of Science, International Islamic University Malaysia, 2018)
Peat swamp forests provide significant ecological role in the environment, yet remain as poorly studied biotypes. They are mostly under enormous threats of peatland degradation and drainage for development and agriculture. In the South-East Pahang Peat Swamp Forest (SEPPSF), Malaysia, a microbial ecology exploration was commenced by primarily unravelling the assemblages of microbial community associated with peat soil using next-generation sequencing approach. In this report, the diversity and structure of microbial community which are bacteria, archaea and fungi associated with peat soil at 0 cm (surface) and 50 cm (deep) depths were described. The preliminary physicochemical analysis indicated that the peat soil was acidic (average pH = 3.43 ± 0.32), soggy (average moisture 64.6 ± 5.7%) and unprecedentedly sandy with average ratio 9.9 ± 5.2 of sand to clay content. Bioinformatic analysis of 16S and 18S rRNA gene fragments identified 28,480 bacterial OTUs and 13,793 fungal OTUs at 97% sequence similarity, inhabiting the surface and deep soils. Archaeal phylotypes were observed at both surface and deep soils although the percentage relative abundance was slightly higher in deep soils. Thaumarchaeota and Euryarchaeota dominated the archaeal phylotypes across all samples. The majority of bacterial phylotypes were affiliated with Acidobacteria, Proteobacteria, and Actinobacteria while fungal phylotypes were mainly comprised of Tremellaceae and Saccharomycetes taxonomic groups. Interestingly, there was a large percentage of relative abundance affiliated with unassigned fungal groups, which are taxonomically ambiguous in every sample especially in S10 which was 65.23 %. The average value of Good´s coverage index for 16S and 18S amounted to 92.9 ± 1.9 % and 98.2 ± 0.5 % respectively. ANOSIM results based on unweighted UniFrac distance matrix indicated no significant difference (P > 0.05) between microbial communities inhabiting surface and deep soils. However, based on location A and B where the later comprised of peats with higher clay content, the microbial communities showed significant difference (P < 0.05). These findings could bridge the gap between cultivation and non-cultivation-based studies on SEPPSF soils microbiome.